Membangun Citra Organisasi: Studi Kasus Kantor Wali Nagari Talang Babungo Kabupaten Solok - Putri, Trany Septirahayu; Dewi, Rahmi Surya; Asmawi, Asmawi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
The aim of this research is to describe organizational communication and analyze image formation at the Wali Nagari Talang Babungo Office using qualitative research methods within the constructivist paradigm and analyzing it through the lens of Organizational Control theory. The study reveals that organizational communication within the Talang Babungo mayor's office encompasses both internal and external interactions. Internally, communication processes are continuous and are facilitated by the use of digital technology. Externally, communication occurs during service delivery and community engagement activities, involving both community members and nagari officials who actively participate in various events and sustainable development initiatives in Nagari Talang Babungo. Efforts to shape the organizational image are evident through the implementation of work processes, service delivery, and development initiatives. These efforts contribute to the positive perception of the Wali Nagari Talang Babungo Office within the community, enhancing its reputation and fostering trust among stakeholders.